Bystander Position Taking in School Bullying: The Role of Positive Identity, Self-Efficacy, and Self-Determination - Sandra K. M. Tsang; Eadaoin K. P. Hui; Bella C. M. Law (The Scientific World Journal)
School bullying has become an explicit, burgeoning problem challenging the healthy development of children and adolescents in Hong Kong. Many bullying prevention and intervention programs focus on victims and bullies, with bystanders treated as either nonexistent or irrelevant. This paper asserts that bystanders actually play pivotal roles in deciding whether the bullying process and dynamics are benign or adversarial. Bystanders' own abilities and characteristics often influence how they respond to victims and bullies. “P.A.T.H.S. to Adulthood: A Jockey Club Youth Enhancement Scheme” (P.A.T.H.S. = Positive Adolescent Training through Holistic Social Programmes) is an evidence-based positive youth development program which shows that primary intervention programs have constructive impacts on junior secondary school students' beliefs and behavior. This paper asserts that intrapsychic qualities, namely identity, self-efficacy, and self-determination, greatly influence how bystanders react in school bullying situations. The paper also explains how classroom-based educational programs based on the P.A.T.H.S. model have been designed to help junior secondary school students strengthen these characteristics, so that they can be constructive bystanders when they encounter school bullying.